New data on the distribution of aquatic bugs (Hemiptera) from eastern Morocco with notes on chorology - Taybi, Abdelkhaleq Fouzi; Mabrouki, Youness; Chavanon, Guy; Berrahou, Ali; Millán, Andrés (Zootaxa, 2018)
New faunistic and distributional data on aquatic Hemiptera from the Oriental Region of Morocco and the Moulouya River basin, covering an area of 119,268 km2, are presented. An annotated list of 45 species, 21 genera and 11 families is provided. Nine species are new records for the entire studied area, and two for the Moulouya River basin. We rediscovered Velia noualhieri iberica and Notonecta viridis after eight decades. We also provide novel records for Aphelocheirus pemae and Hebrus atlas, which were recently described from Morocco, and for the invasive corixid Trichocorixa verticalis verticalis. The dominance of species with broad distributions points to the high dispersal dynamics of the Hemiptera community in the study area, similar to that of other areas where a semiarid climate prevails.